Heat of hydration, bleeding, viscosity, setting of Ca(OH)2-GGBS and MgO-GGBS grouts. (8th February 2021) - Yu, Hua; Yi, Yaolin; Unluer, Cise
Highlights: Properties of Ca(OH)2 -GGBS and MgO-GGBS grouts were investigated. Compared with MgO, Ca(OH)2 was more effective on activating GGBS in short term. Effect of activator/GGBS ratio on viscosity of grouts was limited when W/C ratio ≥ 1. Bleeding and setting times of MgO-GGBS grouts were lower due to hydration of MgO. Abstract: Hydrated lime (Ca(OH)2 )- and reactive magnesia (MgO)-activated ground granulated blast-furnace slag (GGBS) have shown advantages in geotechnical applications compared with Portland cement (PC). To apply these two novel binders in slurry form to field applications, the properties of their grouts need to be investigated, which is the objective of this study. The heat of hydration, bleeding, viscosity, and setting behavior of Ca(OH)2 -GGBS and MgO-GGBS grouts were investigated and compared with PC and pure GGBS grouts in this study. All grouts indicated a decrease in bleeding and setting time, but an increase in viscosity with decreasing the water/cementitious material (W/C) ratio. Compared with the PC grout, the pure GGBS grout with the same W/C ratio demonstrated higher bleeding and setting time, and lower heat rate and viscosity. Bleeding and setting time decreased and peak heat rate and viscosity increased with an increase in the activator (Ca(OH)2 or MgO)/GGBS ratio within GGBS-based grouts. The peak heat rate in Ca(OH)2 -GGBS grouts was higher than that of pure GGBS or Ca(OH)2 grout, indicating that Ca(OH)2 was effective on activating hydration of GGBS. The peak heat rate in MgO-GGBS grouts was significantly lower than MgO grout and the heat rate was limited after 8 h. The bleeding and setting times of MgO-GGBS grouts were significantly lower than those of Ca(OH)2 -GGBS grouts, which was primarily attributed to the hydration of MgO.